Forest Return on an Abandoned Field – Secondary Succession Under Monitored Conditions - Adamowski, Wojciech; Bomanowska, Anna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The secondary succession pattern observed on an arable field abandoned since 1974 in Tilio-Carpinetum habitat is described and disscussed. Results obtained during 36 years of study confirm that succession on an abandoned field leads from a typical segetal community to the formation of a juvenile treestand composed of pioneer species. Our study supports the view that succession is a process which is largely dependent on the initial conditions and surrounding vegetation. The results indicate that some species can modify the course of this process, accelerating or slowing it down. Limitations of the method and prognosis of future vegetation development are also discussed.